Crime prevention : programs, policies and practices - Barkan, Steven E. 1951-; Rocque, Michael (Los Angeles : SAGE Publications, Inc, 2021)
"Crime continues to be a significant problem in the United States despite a large drop since the early 1990s. In this book, renown scholars Steven E. Barkan and Michael A. Rocque present a well-rounded exploration of crime prevention theories and evidence-based policies, programs, and practices. Grounded in criminological theory, while also critically examining the social roots of crime, such as economics and employment, this text presents the current research, perspectives, and examples that capture the key crime prevention concepts students should understand, including the public health model for crime prevention. Emphasizing the importance of application, the author integrate theory and practice through the use of program reviews throughout the text and connect the concepts covered to the real world"--
Includes bibliographical references.
Keywords: Crime prevention